DINAMIKA PERMASALAHAN KETENAGAKERJAAN DAN PENGANGGURAN DI INDONESIA (Administratio, 2019)
This paper attempts to discuss employment and unemployment issues. The problem of unemployment needs to be reduced and create jobs in order to increase and accelerate the country's economic growth. Creating a labor market is the key to ease in doing business. The implementation of policies in Indonesia so far does not provide convenience for the private sector and the world in carrying out their business. A number of things are constraints, namely long licensing, expensive costs and long processing times because it can interfere with the creation of quality work field work. The institutional aspect is a key element that needs to be improved in an effort to reduce unemployment. Beside that, the importance of institutional aspects in solving development problems by creating and expanding employment opportunities. Institutional legal aspects need to be made arrangements for public goods in formal and non-formal rules. Keywords: Employment, Unemployment and Institutional